2023
DOI: 10.1186/s12890-023-02310-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD-L1 through evolution phase from pre-invasive to invasive lung adenocarcinoma

Abstract: Background This study evaluated programmed cell death-ligand 1 (PD-L1) expression from pre-invasive adenocarcinoma to invasive lung adenocarcinoma, aimed to investigate the potential association of PD-L1 pathway with lung adenocarcinoma early evolution. Methods We evaluated PD-L1 expression in 1123 resected lung specimens of adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA) and invasive adenocarcinoma (IAC) of stage IA1–IA3. PD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Furthermore, Ki67 was the dominant factor influencing the expression of PD-L1. It was suggested by J. Zhou et al [41] that reduced PD-L1 expression in AIS or MIA was due to the low expression of Ki67 and that advanced stage LUAD corresponded to high expression of Ki67. Meta-analysis has indicated that high Ki-67 expression is a valuable predictor for advanced TNM stages [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ki67 was the dominant factor influencing the expression of PD-L1. It was suggested by J. Zhou et al [41] that reduced PD-L1 expression in AIS or MIA was due to the low expression of Ki67 and that advanced stage LUAD corresponded to high expression of Ki67. Meta-analysis has indicated that high Ki-67 expression is a valuable predictor for advanced TNM stages [9].…”
Section: Discussionmentioning
confidence: 99%
“…High eukaryotic initiation factor 3 (eIF3D) expression is independently associated with lower OS probability in LUAD [ 11 ]. Programmed death-ligand 1 (PD-L1) expression was positively correlated with the emergence of invasiveness and pathological subtype or biological behavior of early-stage lung adenocarcinoma [ 12 ]. However, these biomarkers are currently insufficient for the diagnosis and prognosis prediction of LUAD because of their complex molecular mechanisms and disease heterogenicity.…”
Section: Introductionmentioning
confidence: 99%